Peran Kelompok Tani dalam Meningkatkan Pendapatan Masyarakat di Desa Alkani Kecamatan Wewiku Kabupaten Malaka - Mersiana Ari Tetik; Yoakim Rembu; Agustinus Longa Tiza; Stefanus Bekun (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The focus of this study is to analyze how the position and role of farming communities contribute to increasing community income in Alkani Village, Wewiku Subdistrict, Malaka Regency. Using a qualitative research method covering research accuracy, focus, data sources, data collection techniques, and data analysis the study describes how farmer groups function as a platform for sharing agricultural information and improving economic outcomes. Findings show that these groups actively facilitate knowledge exchange by introducing modern technologies such as tractors and drip-irrigation systems, and by promoting digital marketing to expand market access. Farmer groups in Alkani Village also serve as regular discussion forums, holding monthly or needs-based meetings where members communicate, share experiences, and address agricultural challenges together. Through training, cooperation, and collective learning, farmer groups operate not only as centers for education but also as agricultural production units that strengthen the local farming sector. Their role in collaboration enhances solidarity among farmers, enabling them to support one another and work more efficiently. As a result, these groups significantly contribute to increasing farmers’ income and improving overall welfare. The study concludes that strengthening farmer groups is essential, recommending continued enhancement of training access, administrative capacity, and active participation from all members to ensure equitable benefits.